AGREE‐S: AGREE II extension for surgical interventions – United European Gastroenterology and European Association for Endoscopic Surgery methodological guide. Issue 4 (4th May 2022) - Logullo, Patricia; Florez, Ivan D; Antoniou, George A; Markar, Sheraz; López‐Cano, Manuel; Silecchia, Gianfranco; Tsokani, Sofia; Mavridis, Dimitrios; Brouwers, Melissa; Antoniou, Stavros A; ,
Abstract: Background: The Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument has been developed to inform the methodology, reporting and appraisal of clinical practice guidelines. Evidence suggests that the quality of surgical guidelines can be improved, and the structure and content of AGREE II can be modified to help enhance the quality of guidelines of surgical interventions. Objective: To develop an extension of AGREE II specifically designed for guidelines of surgical interventions. Methods: In the tripartite Guideline Assessment Project (GAP) funded by United European Gastroenterology and the European Association for Endoscopic Surgery, (i) we assessed the quality of surgical guidelines and we identified factors associated with higher quality (GAP I); (ii) we applied correlation analysis, factor analysis and the item response theory to inform an adaption of AGREE II for the purposes of surgical guidelines (GAP II); and (iii) we developed an AGREE II extension for surgical interventions, informed by the results of GAP I, GAP II, and a Delphi process of stakeholders, including representation from interventional and surgical disciplines; the Guideline International Network (GIN); the Grading of Recommendations Assessment, Development and Evaluation (GRADE) Working Group; the Enhancing the QUAlity and Transparency Of health Research (EQUATOR) initiative; and representation of surgical journal editors and patient/public. Results: We developed AGREE‐S, an AGREE II extension for surgical interventions, which comprises 24 items organized in 6 domains; Scope and purpose, Stakeholders, Evidence synthesis, Development of recommendations, Editorial independence, and Implementation and update. The panel of stakeholders proposed 3 additional items: development of a guideline protocol, consideration of practice variability and surgical/interventional expertise in different settings, and specification of infrastructures required to implement the recommendations. Three of the existing items were amended, 7 items were rearranged among the domains, and one item was removed. The domain Rigour of Development was divided into domains on Evidence Synthesis and Development of Recommendations. The new domain Development of Recommendations incorporates items from the original AGREE II domain Clarity of Presentation. Conclusion: AGREE‐S is an evidence‐based and stakeholder‐informed extension of the AGREE II instrument, that can be used as a guide for the development and adaption of guidelines on surgical interventions.